At cross purposes: Islam and the crucifixion of Christ, a theological response. (July 2017) - Neely, Brent
The paper relates to the classic issue of Islam and the Cross of Christ. It is in two parts. The first part tackles the "textual" issues of the crucifixion (or not) in the Qur'an and tafsir, including some of the "minority reports" in Islamic thought. The second part moves on to a Christian theological engagement with the mainstream Islamic (if not qur'anic) denial of the crucifixion of the Messiah. Some of this section springboards off of the well-known discussion of these issues by Kenneth Cragg and others, but (perhaps) the most original emphasis in this "theological" half of the paper is the attempt to bring the Christus Victor model of the Atonement into interaction with Islamic denials of the cross of Christ.